GE_GERICHTE P/21723/2015 vom 27. Oktober 2016 - GE Cour de justice (2016)
ESCROQUERIE ; FAUX DANS LES CERTIFICATS ; CLASSEMENT DE LA PROCÉDURE ; SOUPÇON ; CAS BÉNIN ; ADMINISTRATION DES PREUVES | CPP.382; CPP.319; CP.52; CP.251; CP.146